Effect of Proportion of Flesh and Peel of Bligo (Benincasa Hispida) on The Organoleptic Characteristics of Bligo Pudding : Pengaruh Proporsi Daging dan Kulit Buah Bligo (Benincasa Hispida) Terhadap Karakteristik Organoleptik Puding Bligo - Mutaqqien, Hexandria Abdullah; Nurbaya, Syarifa Ramadhani; Saidi, Ida Agustini; Budiandari, Rahmah Utami (jurnal makanan tropis dan teknologi agroindustri, 2023)
Bligo plant (Benincasa hispida) is a plant that is still in the same family as the Cucurbitaceae plant. This study utilized the pulp and peel of the bligo fruit (Benincasa hispida) to make pudding using various proportions, consisting of 6 treatment levels (proportion of bligo pulp with bligo peel are 100% : 0%, 80% : 20%, 60% : 40%, 40% : 20%, 0% : 100% . Data were analyzed using Friedman test, ANOVA statistical analysis and 5% BNJ follow-up test. The best treatment was the concentration of the proportion of bligo pulp and peel which showed in P3 treatment (bligo pulp 60% bligo peel 40%) with a color organoleptic test value of 2,47 (normal-like), aroma organoleptic test of 2,20 (normal-like), texture organoleptic test 3,23 (normal-like), and taste organoleptic test 2.83 (normal-like).